Existence and regularity of optimal solution for a dead oil isotherm problem - Ammi, M.R.S. (2011)
We study a system of nonlinear partial differential equations resulting from the traditional modelling of oil engineering within the framework of the mechanics of a continuous medium. Existence and regularity of the optimal solutions for this system is established. © Balkan Society of Geometers, Geometry Balkan Press 2007.